Comparison of Endurance, Agility, and Strength in Elite Hockey and Soccer 9 Year-Old Players - Eryk Przysucha; Carlos Zerpa; Christopher Piek (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Regardless of the age, elite athletes exhibit various motor capabilities (e.g., speed; endurance; strength) that are specific to that particular sport. Objectives. The purpose of this study was to compare different aspects of physical fitness (agility, strength, endurance) in thirty, 9 year old elite soccer and hockey players. Methods. Participants completed a 90 minute familiarization session, and returned at the later date to perform tests examining their agility (T-test), endurance (20mSRT), and strength (long jump; v-ups; push-ups; sit-ups). The tests were administered by an expert trainer at the same location. At the onset no inter-group differences were found for age, height, weight, foot size, number of years playing at the competitive level, and hours training per week, as well as scores from MABC assessment tool. Results. A series of independent sample t-tests revealed statistical differences in endurance (p < .001, d = 3.57), and in strength tasks (p < .001, d = 1.66) (sit-ups, push-ups and v-ups) in favour of soccer group. However, hockey players were more agile (p < .001, d = 1.26) and generated more power as inferred from the long jump (p < .05, d = 1.1). Conclusion. Overall, the results showed that some domains of movement proficiency are specific to either soccer (endurance/ strength) or hockey (agility/power). These results provided coaches with information in regards to their respective teams as well as individual players' performance, and may aid in adaptations of the respective training programmes.